THE EFFECTS OF LANGUAGE INPUT, LEARNING ENVIRONMENT, AND MOTIVATION TOWARD SECOND LANGUAGE ACQUISITION - Baroto, Muhammad Ali Agung (English Department of Faculty of Tarbiyah and Teacher Training, 2016)
In L2 learning process, the role of language input has been of foremost importance in much SLA research and theory. Second language acquisition is influenced by several aspects. Three of them are language input, learning environment and motivation. This study aims to find out the effects of language input, learning environment, and motivation toward second language acquisition. The subject is a fresh graduate of senior high school. The data was collected through interview and questionairre. This study discovered that each of them has effects in learner language, specifically in English speaking proficiency, in terms of fluency and accuracy.